Efforts to Enhance Learning Activity and Conceptual Understanding among Grade XI Students at SMA IT Al Fityah Using the ICARE Model on the Topic of Salt Hydrolysis - Nurul Khafizah; Lenny Anwar; Dedi Futra (Darul Yasin Al Sys, 2026)
Salt hydrolysis instruction presents persistent challenges in promoting active participation and conceptual understanding among chemistry students. This study aimed to improve the learning activity and conceptual understanding of 26 Grade XI science students at SMA IT Al Fityah Pekanbaru through the ICARE learning model. A collaborative classroom action research design was implemented across two cycles, each comprising two meetings and the stages of planning, action, observation, and reflection. Data were collected through observation sheets assessing teacher and student activities, documentation, evaluations conducted after each meeting, and conceptual understanding tests administered at the end of each cycle. The data were analyzed descriptively using activity percentages, individual scores, class mastery rates, and achievement across seven indicators of conceptual understanding. The numbers of students who did not meet the mastery criterion and the lowest scores in each cycle were also examined to assess the distribution of learning outcomes. Instructional improvements emphasized participation, group discussion, reflection, and independent application of concepts. Student learning activity increased from 64.47% in Cycle I to 76.68% in Cycle II, representing an increase of 12.21 percentage points. The mean conceptual understanding score rose from 76.35 to 88.08, while the mean class score increased from 76.34 to 88.27. Class mastery improved from 69.22% to 88.46%. By Cycle II, all seven conceptual understanding indicators had reached at least 84.62%, with the ability to restate concepts reaching 100%. These findings demonstrate that ICARE can improve students’ engagement and conceptual understanding of salt hydrolysis. The model therefore offers a viable student-centered approach to chemistry instruction, provided that teachers ensure effective time management, reinforce prerequisite concepts, and distribute participation equitably.